Preparation method and application of coffee grounds biomass composite material
By combining coffee grounds with unsaturated sulfur vacancy defective molybdenum disulfide nanosheets, solvent-thermal carbon-molybdenum sulfide coffee ground biomass composite materials were prepared by solvent thermal carbonization method, which solved the problems of high energy consumption and poor stability in the prior art, and achieved the effect of efficient adsorption of hexavalent chromium in sewage and resource utilization.
Patent Information
- Application Number
- CN202310987095.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-08-07
AI Technical Summary
The energy consumption and poor stability of existing composite materials are high during the preparation process, making it difficult to effectively utilize coffee grounds to resource utilization, and it is also highly polluted to the environment.
By combining coffee grounds with unsaturated sulfur vacancy defective molybdenum disulfide nanosheets, solvent-thermal carbon-molybdenum sulfide coffee ground biomass composite was prepared by solvent-thermal carbonization method to adsorb hexavalent chromium in wastewater.
It significantly reduces the energy consumption of the preparation process, improves the stability and adsorption capacity of the material, and has an extremely high adsorption capacity for hexavalent chromium in wastewater, achieving the purpose of waste control and protecting the environment.
Smart Images

Figure CN116870866B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomass waste resource utilization, and in particular to a preparation method and application of a coffee grounds biomass composite material. Background Art
[0002] Hexavalent chromium (Cr(VI)) is a highly toxic heavy metal commonly found in industrial wastewater. Excessive discharge into the environment can seriously pollute the environment and threaten human health. In water media, chromium mainly exists in the form of Cr(III) and Cr(VI). At trace levels, Cr(III) is beneficial to the human body, while Cr(VI) is 500-1000 times more toxic than Cr(III). It can accumulate in the human body through the food chain and cause harm to the environment and human health even at trace levels.
[0003] Coffee grounds (SCG) are solid residues produced during the brewing process of instant coffee and coffee, accounting for about 45% of coffee berries. About 6 million tons of coffee grounds are produced every year in the world. Coffee grounds are rich in cellulose and hemicellulose, lignin, protein and a small amount of lipids, and have the potential for resource utilization. However, the resource utilization of coffee grounds is not ideal, and most of them are abandoned, which not only wastes resources but also pollutes the environment.
[0004] For example, patent document CN109603810B discloses a method for preparing a molybdenum disulfide nanosheet / porous graphitized biochar composite material, wherein the biochar preparation process requires potassium permanganate soaking and high-temperature pyrolysis, and the preparation process is cumbersome and energy-intensive, which is not conducive to large-scale production. Patent document CN110548487B discloses a hydrothermal carbon composite material combined with a metal organic framework, which effectively improves the stability of the material, but requires the use of solvents such as copper nitrate and formic acid in the process of preparing the metal organic framework, and its preparation process is less green, which is not conducive to environmental protection. Therefore, the development of a method for preparing a coffee grounds biomass composite material and its application is not only conducive to the utilization of biomass waste, but also to environmental safety. Summary of the invention
[0005] The main purpose of the present invention is to provide a preparation method and application of a coffee grounds biomass composite material, aiming to prepare a solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material using waste coffee grounds and molybdenum sulfide, and use it to adsorb hexavalent chromium in sewage.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a coffee grounds biomass composite material comprises the following steps:
[0008] (1) Soaking coffee grounds in water, drying and sieving to obtain pretreated coffee grounds;
[0009] (2) adding ammonium molybdate tetrahydrate and thiourea into deionized water and mixing them uniformly to obtain a mixed solution A; and dispersing the mixed solution A by ultrasonication to obtain a precursor mixed solution;
[0010] (3) placing the precursor mixed solution in step (2) in a reactor for hydrothermal reaction, and cooling naturally after the reaction is completed to obtain a reaction solution A; filtering the reaction solution A to obtain a filter residue A, washing, drying and then grinding the filter residue to obtain a molybdenum disulfide nanosheet with unsaturated sulfur vacancy defects;
[0011] (4) adding the pretreated coffee grounds in step (1) and the molybdenum disulfide nanosheets with unsaturated sulfur vacancy defects in step (3) into a solvent and mixing them evenly to obtain a mixed solution B;
[0012] (5) After ultrasonically dispersing the mixed solution B in step (4), placing it in a reactor for a solvent thermal reaction, and naturally cooling it after the reaction is completed to obtain a reaction solution B; filtering the reaction solution B to obtain a filter residue B, and washing and drying the filter residue B to obtain a solvent thermal carbon-molybdenum sulfide coffee residue biomass composite material.
[0013] By adding prepared molybdenum disulfide nanosheets with unsaturated sulfur vacancy defects during the solvent thermal carbon generation process, while the biomass is pyrolyzed, the molybdenum disulfide nanosheets are in-situ grown on the solvent thermal carbon framework, anhydrous ethanol is used as a solvent to reduce the total energy of defective molybdenum disulfide, and a large number of hydroxyl groups are introduced on the solvent thermal carbon. Through the secondary solvent thermal treatment, the molybdenum sulfide is stabilized while the biomass is cracked and the molybdenum sulfide is loaded, which can significantly reduce energy consumption. At the same time, the biomass is the waste coffee grounds generated in the coffee production process, which has a wide source and low cost; the solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material prepared from the waste coffee grounds and molybdenum sulfide has a high stability and a very high adsorption capacity for hexavalent chromium in wastewater, thereby solving the problems of high energy consumption and poor stability in the preparation process of the existing composite materials, and achieving the purpose of treating waste with waste.
[0014] Preferably, the solid-to-liquid ratio of the coffee grounds to water in step (1) is 1:2-5 g / mL.
[0015] Preferably, the molar ratio of ammonium molybdate tetrahydrate to thiourea in step (2) is 1:14-28.
[0016] Preferably, the hydrothermal reaction in step (3) is carried out at 170-190° C. for 12-24 hours.
[0017] Preferably, in step (4), the mass ratio of the pretreated coffee grounds to the molybdenum disulfide nanosheets with unsaturated sulfur vacancy defects is 1:0.3-0.5; and the solvent is anhydrous ethanol.
[0018] Preferably, the solvent thermal reaction in step (5) is carried out at 200-250° C. for 4-12 hours.
[0019] Preferably, the drying in step (1), step (3) and step (5) is performed at 60-100° C. for 12-24 hours; and the washing in step (3) and step (5) is performed by alternating washing with deionized water and anhydrous ethanol until the washing liquid is clear.
[0020] Preferably, the particle size of the pretreated coffee grounds in step (1) and the molybdenum disulfide nanosheets with unsaturated sulfur vacancy defects in step (3) are both 0.1 to 1.0 mm; and the ultrasonic dispersion time in steps (2) and (5) is both 10 to 30 min.
[0021] A coffee grounds biomass composite material is prepared by the above-mentioned coffee grounds biomass composite material preparation method.
[0022] The coffee grounds biomass composite material is used for adsorbing hexavalent chromium in sewage.
[0023] The solvent hot carbon-molybdenum sulfide coffee grounds biomass composite material is used to adsorb Cr(VI) in water, comprising the following steps: mixing the solvent hot carbon-molybdenum sulfide coffee grounds biomass composite material with water containing Cr(VI), and completing the adsorption treatment of Cr(VI) in water after reaching adsorption equilibrium. The mass volume ratio of the solvent hot carbon-molybdenum sulfide coffee grounds biomass composite material to the Cr(VI)-containing wastewater is (0.1-0.5) g:1 L. During the experiment, potassium dichromate is used to provide Cr(VI) in the Cr(VI)-containing wastewater, and the concentration of Cr(VI) in the Cr(VI)-containing wastewater is 10-100 mg / L; the adsorption time is 24-48 hours.
[0024] The beneficial effects of the present invention are:
[0025] 1. The present invention uses solvent thermal carbonized coffee grounds as a carrier to in-situ load stabilized defective molybdenum disulfide nanosheets on its surface; in the present invention, the pyrolyzed biomass has a porous structure and a large specific surface area, and has a good adsorption capacity for pollutants; in this regard, by in-situ growing defective molybdenum disulfide nanosheets on the surface of solvent thermal carbon and stabilizing them, a composite material adsorbent with excellent performance and stable properties can be obtained.
[0026] 2. The present invention uses the waste coffee grounds produced in the coffee production process as a solvent thermal carbon precursor to prepare solvent thermal carbonized biochar as a carrier, loads defective molybdenum disulfide nanosheets onto the solvent thermal carbon framework, and prepares a composite material with high adsorption capacity and strong stability. In the present invention, the selected materials are widely available and low in cost, which improves the utilization rate of by-products in the food industry; the biochar is prepared by solvent thermal carbonization, and anhydrous ethanol is used as a solvent. While reducing energy consumption, a large number of hydroxyl groups can be introduced on the solvent thermal carbon framework to improve the adsorption capacity of heavy metals; the defective molybdenum disulfide nanosheets are loaded onto the solvent thermal carbon framework, and anhydrous ethanol is used as a solvent, which can greatly reduce the total energy of the composite material, and stabilize the material while retaining a large number of adsorption sites.
[0027] 3. The preparation method of the present invention has simple process, low energy consumption, low cost, and does not produce toxic or harmful by-products during the preparation process. It can be mass-produced and meets the requirements of environmental protection.
[0028] 4. The solvent hot carbon-molybdenum sulfide composite material prepared by the present invention can be used to treat heavy metal Cr(VI) in sewage. By mixing the solvent hot carbon-molybdenum sulfide composite material with sewage containing Cr(VI), the Cr(VI) in the water body can be efficiently removed by a constant temperature water bath shaker, and the removal rate can reach more than 95%, which can effectively remove Cr(VI) in environmental water bodies. In addition, the composite material has a high degree of stability, will not cause secondary pollution to the environment, and is safe and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope image of the solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material prepared in Example 1 of the present invention;
[0030] Figure 2 This is a transmission electron microscopy image of the solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material prepared in Example 1 of the present invention;
[0031] Figure 3 This is a diagram showing the efficiency of the solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material for adsorbing hexavalent chromium. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0033] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0034] Example 1
[0035] This embodiment provides a method for preparing a solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material, comprising the following steps:
[0036] (1) Coffee grounds pretreatment
[0037] Soak 100 g of coffee grounds in 300 mL of water for 10 min. After solid-liquid separation, dry the filter residue at 80° C. for 18 h, grind it, and sieve it to obtain pretreated coffee grounds with a particle size of less than 1 mm.
[0038] (2) Preparation of defective MoS2 nanosheets
[0039] 2.72 g of ammonium molybdate tetrahydrate and 4.94 g of thiourea (molar ratio 1:28) were added into deionized water, mixed evenly under magnetic stirring, and evenly dispersed in an ultrasonic cleaner for 20 min to obtain a precursor mixed solution; the precursor mixed solution obtained above was transferred into a stainless steel reactor with a polytetrafluoroethylene liner, and reacted at 180°C for 24 h; after the reaction was completed, it was naturally cooled, filtered and washed alternately three times with anhydrous ethanol and deionized water to obtain a black solid, which was dried at 60°C and ground to obtain defective molybdenum disulfide nanosheets with a particle size of less than 1 mm.
[0040] (3) Biomass solvent thermal carbonization synergistic with MoS2 stabilization and loading
[0041] 0.5 g of molybdenum disulfide nanosheets and 1 g of waste coffee grounds were added to anhydrous ethanol, mixed evenly under magnetic stirring, and evenly dispersed in an ultrasonic cleaner for 20 min; the mixed solution obtained above was transferred into a stainless steel reactor with a polytetrafluoroethylene liner and reacted at 250°C for 12 h; after the reaction, it was naturally cooled, and the filter residue obtained by filtration was washed alternately with anhydrous ethanol and deionized water three times, and dried at 60°C to obtain a black solid with metallic luster. The corresponding solvent hot carbon-molybdenum sulfide composite material was named 1T-MoS 2 @STC.
[0042] The prepared solvent thermal carbon-molybdenum sulfide composite material was subjected to scanning electron microscopy. The results are as follows Figure 1 As shown. Figure 1It can be seen that the surface of the solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material is inlaid with a large number of nanoflower-like substances, which proves the successful loading of molybdenum sulfide on the solvent thermal carbon surface. The exposed lamellar structure can effectively increase the number of active sites and greatly enhance the adsorption effect.
[0043] The prepared solvent hot carbon-molybdenum sulfide composite material was subjected to transmission electron microscopy. The results are as follows Figure 2 As shown. Figure 2 A specific lattice spacing of MoS2 (0.96 nm) can be observed, demonstrating the successful loading of MoS2 on the surface of the solvothermal carbon. The wider lattice spacing allows the chromium ion groups to enter the MoS2 layer, improving the adsorption effect.
[0044] Example 2
[0045] This embodiment provides a method for preparing a solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material, comprising the following steps:
[0046] (1) Coffee grounds pretreatment
[0047] Soak 100 g of coffee grounds in 500 mL of water for 10 min. After solid-liquid separation, dry the filter residue at 100° C. for 12 h, grind it, and sieve it to obtain pretreated coffee grounds with a particle size of less than 1 mm.
[0048] (2) Preparation of defective MoS2 nanosheets
[0049] 1.1 g of ammonium molybdate tetrahydrate and 1.35 g of thiourea (molar ratio 1:20) were added to deionized water, mixed evenly under magnetic stirring, and evenly dispersed in an ultrasonic cleaner for 30 min to obtain a precursor mixed solution; the precursor mixed solution obtained above was transferred into a stainless steel reactor with a polytetrafluoroethylene liner, and reacted at 190°C for 12 h; after the reaction was completed, it was naturally cooled, filtered and washed alternately three times with anhydrous ethanol and deionized water to obtain a black solid, which was dried at 100°C and ground to obtain defective molybdenum disulfide nanosheets with a particle size of less than 1 mm.
[0050] (3) Biomass solvent thermal carbonization synergistic with MoS2 stabilization and loading
[0051] 0.4 g of molybdenum disulfide nanosheets and 1 g of waste coffee grounds were added to anhydrous ethanol, mixed evenly under magnetic stirring, and evenly dispersed in an ultrasonic cleaner for 30 min; the mixed solution obtained above was transferred into a stainless steel reactor with a polytetrafluoroethylene liner and reacted at 230°C for 8 h; after the reaction was completed, it was naturally cooled, and the filter residue obtained by filtration was washed alternately three times with anhydrous ethanol and deionized water, respectively, and dried at 100°C to obtain a black solid solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material with metallic luster.
[0052] Example 3
[0053] This embodiment provides a method for preparing a solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material, comprising the following steps:
[0054] (1) Coffee grounds pretreatment
[0055] Soak 100 g of coffee grounds in 200 mL of water for 10 min. After solid-liquid separation, dry the filter residue at 60° C. for 18 h, grind it, and sieve it to obtain pretreated coffee grounds with a particle size of less than 1 mm.
[0056] (2) Preparation of defective MoS2 nanosheets
[0057] 2.0 g of ammonium molybdate tetrahydrate and 1.72 g of thiourea (molar ratio 1:14) were added into deionized water, mixed evenly under magnetic stirring, and evenly dispersed in an ultrasonic cleaner for 10 min to obtain a precursor mixed solution; the precursor mixed solution obtained above was transferred into a stainless steel reactor with a polytetrafluoroethylene liner, and reacted at 170°C for 18 h; after the reaction was completed, it was naturally cooled, filtered and washed alternately three times with anhydrous ethanol and deionized water to obtain a black solid, which was dried at 60°C and ground to obtain defective molybdenum disulfide nanosheets with a particle size of less than 1 mm.
[0058] (3) Biomass solvent thermal carbonization synergistic with MoS2 stabilization and loading
[0059] 0.3 g of molybdenum disulfide nanosheets and 1 g of waste coffee grounds were added to anhydrous ethanol, mixed evenly under magnetic stirring, and evenly dispersed in an ultrasonic cleaner for 10 min; the mixed solution obtained above was transferred into a stainless steel reactor with a polytetrafluoroethylene liner and reacted at 200°C for 4 h; after the reaction was completed, it was naturally cooled, and the filter residue obtained by filtration was washed alternately three times with anhydrous ethanol and deionized water, respectively, and dried at 60°C to obtain a black solid solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material with metallic luster.
[0060] Example 4
[0061] Effect of different mass ratios of pretreated coffee grounds and MoS2 nanosheets containing unsaturated sulfur vacancy defects on Cr(VI) removal efficiency
[0062] The preparation method of the solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material of this embodiment 4 is different from that of embodiment 1 in that 0.1g, 0.2g, 0.3g, 0.4g, 0.5g of molybdenum disulfide nanosheets and 1g of waste coffee grounds are added to anhydrous ethanol. The corresponding solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite materials are numbered as MoS 2 / STC 1、MoS 2 / STC 2 、MoS 2 / STC 3 、MoS 2 / STC 4 、MoS 2 / STC 5 .
[0063] The application of solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material in the treatment of sewage adsorption of Cr (VI), specifically, the solvent thermal carbon-molybdenum sulfide coffee grounds biomass composite material (MoS 2 / STC 1 、MoS 2 / STC 2 、MoS 2 / STC 3 、MoS 2 / STC 4 、MoS 2 / STC 5 ) is used to treat Cr(VI) in sewage, comprising the following steps:
[0064] Solvothermal carbon-molybdenum sulfide coffee grounds biomass composite (MoS 2 / STC 1 、MoS 2 / STC 2 、MoS 2 / STC 3 、MoS 2 / STC 4 、MoS 2 / STC 5 )50mg, placed in 250ml, Cr(VI) concentration of 50mg / L potassium dichromate solution, reacted for 48h under light-proof conditions. Samples were taken every 30min to determine the Cr(VI) concentration in the solution, and the removal efficiency of the solvent thermal carbon-molybdenum sulfide composite material for Cr(VI) was calculated. The results are shown in Figure 3 -The efficiency diagram of the solvent hot carbon-molybdenum sulfide composite material for adsorbing Cr(VI) is shown in Figure 1, and the effect of the solvent hot carbon-molybdenum sulfide composite material obtained with different mass ratios of raw materials on the Cr(VI) removal rate is shown in Table 1.
[0065] Table 1
[0066]
[0067] From Table 1 and Figure 3It can be seen that with the increase of loading amount, the removal rate of Cr(VI) in the solution by solvent thermal carbon-molybdenum sulfide composite material is constantly increasing. When the mass ratio of molybdenum disulfide nanosheets and waste coffee grounds is 0.4:1 and 0.5:1, the removal rate reaches more than 99%, which indicates that solvent thermal carbon-molybdenum sulfide composite material can significantly reduce the concentration of Cr(VI) in water pollution and reduce damage to the environment.
[0068] In summary, the present invention uses solvent thermal carbonized coffee grounds as a carrier to in-situ load stabilized defective molybdenum disulfide nanosheets on its surface; pyrolyzed biomass has a porous structure and a large specific surface area, and has a good adsorption capacity for pollutants; in this regard, by in-situ growing defective molybdenum disulfide nanosheets on the surface of solvent thermal carbon and stabilizing them, a composite material adsorbent with excellent performance and stable properties can be obtained.
[0069] The specific implementation methods of the invention are described in detail above, but they are only examples, and the invention is not limited to the specific implementation methods described above. For those skilled in the art, any equivalent modification or substitution of the invention is also within the scope of the invention, therefore, the equalization, modification, improvement, etc. made without departing from the spirit and principle of the invention should be included in the scope of the invention.
Claims
1. A method for preparing a coffee grounds biomass composite material for adsorbing hexavalent chromium in sewage, characterized in that: The following steps are involved: (1) Soaking coffee grounds in water, drying and sieving to obtain pretreated coffee grounds; (2) adding ammonium molybdate tetrahydrate and thiourea into deionized water and mixing them evenly to obtain a mixed solution A; The mixed solution A is dispersed by ultrasound to obtain a precursor mixed solution; (3) placing the precursor mixed solution in step (2) in a reactor for hydrothermal reaction, and cooling naturally after the reaction is completed to obtain a reaction solution A; The reaction solution A is filtered to obtain a filter residue A, and the filter residue A is washed, dried, and then ground to obtain a molybdenum disulfide nanosheet with unsaturated sulfur vacancy defects; (4) adding the pretreated coffee grounds in step (1) and the molybdenum disulfide nanosheets with unsaturated sulfur vacancy defects in step (3) into a solvent and mixing them evenly to obtain a mixed solution B; (5) ultrasonically dispersing the mixed solution B in step (4) and placing it in a reactor for solvothermal reaction, and cooling it naturally after the reaction is completed to obtain a reaction solution B; filtering the reaction solution B to obtain a filter residue B, and washing and drying the filter residue B to obtain a solvothermal carbon-molybdenum sulfide coffee grounds biomass composite material; The molar ratio of ammonium molybdate tetrahydrate to thiourea in step (2) is 1:14-28; The mass ratio of the pretreated coffee grounds to the molybdenum disulfide nanosheets with unsaturated sulfur vacancy defects in step (4) is 1:0.3-0.5; the solvent is anhydrous ethanol; The solvent thermal reaction in step (5) is carried out at 200-250° C. for 4-12 hours.
2. The method for preparing the coffee grounds biomass composite material according to claim 1, characterized in that: The solid-to-liquid ratio of the coffee grounds to water in step (1) is 1:2-5 g / mL.
3. The method for preparing the coffee grounds biomass composite material according to claim 1, characterized in that: The hydrothermal reaction in step (3) is carried out at 170-190° C. for 12-24 hours.
4. The method for preparing the coffee grounds biomass composite material according to claim 1, characterized in that: The drying in step (1), step (3) and step (5) is performed at 60 to 100° C. for 12 to 24 hours; the washing in step (3) and step (5) is performed by alternating washing with deionized water and anhydrous ethanol until the washing liquid is clear.
5. The method for preparing the coffee grounds biomass composite material according to claim 1, characterized in that: The particle sizes of the pretreated coffee grounds in step (1) and the molybdenum disulfide nanosheets with unsaturated sulfur vacancy defects in step (3) are both 0.1 to 1.0 mm; and the ultrasonic dispersion time in steps (2) and (5) is both 10 to 30 min.
6. A coffee grounds biomass composite material for adsorbing hexavalent chromium in sewage, characterized in that: The coffee grounds biomass composite material is prepared by the method for preparing the coffee grounds biomass composite material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Molybdenum disulfide nanosheets / porous graphitized biochar composite materials, their preparation methods, and applications.
CN109603810B
A hydrothermal carbon-based composite material, its preparation and application
CN110548487B